PEMAHAMAN MAHASISWA PGMI UIN SYARIF HIDAYATULLAH JAKARTA SEMESTER 3 TERHADAP TUJUAN DAN FUNGSI PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QUR’AN - elisa elisa (STKIP Subang, 2026)
This study aims to find out the extent to which students of the Madrasah Ibtidaiyah (PGMI) program of UIN Syarif Hidayatullah Jakarta Semester 3 understand the purpose and function of Islamic education and how this affects their willingness to teach. This understanding is considered crucial because prospective Islamic education teachers must not only have academic knowledge but also be able to instill Islamic values in their students. This study uses a quantitative descriptive method with a survey. PGMI students were given a questionnaire to collect primary data. The findings of the study show that most students understand the purpose and function of Islamic education. They also understand the relationship between the role of teachers as role models, the development of students' potential, and character building. Their desire to teach increases as a result of this strong understanding. This is seen in their lesson design, their direction, and the application of Islamic values in the classroom. In addition, this study shows that some students need guidance and practice to effectively apply the concept of Islamic education in the classroom.